(untitled) (American Journal of Pedagogical and Educational Research, 2026)
The rapid digital transformation of the global tourism industry has significantly reshaped the competency requirements for tourism professionals. International organizations emphasize that digital skills and artificial intelligence (AI) literacy are becoming core employability factors in tourism and service sectors [1], [2]. However, higher education institutions continue to rely largely on traditional instructional methodologies that insufficiently integrate AI-based digital technologies into professional training. This creates a structural gap between industry expectations and graduate preparedness. Although recent studies examine AI applications in tourism and hospitality [5], [10] and digital innovation in education [3], empirical research proposing a systematic pedagogical model for AI-integrated tourism education remains limited. This study aims to enhance the methodology of professional training for tourism students through an AI-integrated digital learning framework grounded in experiential learning theory [7] and digital competence frameworks [8]. A quasi-experimental design was implemented involving 52 undergraduate tourism students divided into control and experimental groups over one academic semester. The intervention included AI-assisted case analysis, digital itinerary simulations, and competency-based assessment. Statistical analysis using paired-sample t-tests demonstrated significant improvement in the experimental group (p < 0.01), with a large effect size (Cohen’s d = 0.82). The findings confirm that AI-integrated methodology substantially enhances professional and digital competencies, offering a scalable model for modernizing tourism education in alignment with global digital transformation trends [4], [9].